Carved bodies in Singapore : a tattooed youth's view. - Lin, Daphne Hui Lin. (2010)
An ethnographic investigation of tattooed youths in Singapore. The author uses her own experience of getting her first tattoo to explain and point out the discrimination and opposition she faces, along with the joys of a new-found hobby. It is useful to examine how cultural differences mould the different generations’ attitudes and perceptions towards tattoos.